Consequences of GMPPB deficiency for neuromuscular development and maintenance - Schurig, Mona K.; Umeh, Obinna; Henze, Henriette; Jung, M. Juliane; Gresing, Lennart; Blanchard, Véronique; von Maltzahn, Julia; Hübner, Christian A.; Franzka, Patricia (Frontiers in Molecular Neuroscience, 2024)
Guanosine diphosphate-mannose pyrophosphorylase B (GMPPB) catalyzes the conversion of mannose-1-phosphate and GTP to GDP-mannose, which is required as a mannose donor for the biosynthesis of glycan structures necessary for proper cellular functions. Mutations in GMPPB have been associated with various neuromuscular disorders such as muscular dystrophy and myasthenic syndromes. Here, we report that GMPPB protein abundance increases during brain and skeletal muscle development, which is accompanied by an increase in overall protein mannosylation. To model the human disorder in mice, we generated heterozygous GMPPB KO mice using CIRSPR/Cas9. While we were able to obtain homozygous KO mice from heterozygous matings at the blastocyst stage, homozygous KO embryos were absent beyond embryonic day E8.5, suggesting that the homozygous loss of GMPPB results in early embryonic lethality. Since patients with GMPPB loss-of-function manifest with neuromuscular disorders, we investigated the role of GMPPB in vitro. Thereby, we found that the siRNA-mediated knockdown of Gmppb in either primary myoblasts or the myoblast cell line C2C12 impaired myoblast differentiation and resulted in myotube degeneration. siRNA-mediated knockdown of Gmppb also impaired the neuron-like differentiation of N2A cells. Taken together, our data highlight the essential role of GMPPB during development and differentiation, especially in myogenic and neuronal cell types.